Gandhi his triumph changed the world forever - Attenborough, Richard; Kingsley, Ben; Bergen, Candice 1946-; Briley, John (Columbia Pictures, 1982)
A film on the life, principles and power of Mahatma Gandhi, from his beginnings as a South African-educated lawyer, up to his historic, galvanizing struggle to free India from British colonial rule and how he led India to freedom using non-violent methods.